Socio-economy analysis of the community in Kediri City on the implementation of restriction policy of single-use plastic usage - Tarnada Zanuar, Ella Arlaydes; Arseto Yekti Bagastyo (Jurnal Serambi Engineering, 2025)
The increasing use of single-use plastics in Kediri City prompted the issuance of Kediri Mayor Regulation No. 30 of 2023 on restricting single-use plastics. This study analyzes plastic waste composition, community and business participation, and the factors influencing policy implementation. Plastic waste composition was measured using the quarter sampling method in three districts, while participation data were analyzed using Structural Equation Modelling (SEM-PLS). The results show that plastic bags dominate single-use plastic waste, contributing up to 90%, particularly in residential areas due to small business activities. Support for the policy is relatively high, with 74.46% of the community and 64.64% of businesses agreeing, but concrete implementation remains low. SEM-PLS analysis reveals that environmental awareness, knowledge, and attitudes significantly influence the reduction of single-use plastics, while economic income factors are not significant. Continuous education, the provision of eco-friendly alternatives, and collaboration among stakeholders are essential to enhancing policy effectiveness.